Different cut‐off values of the insulin tolerance test, the high‐dose short Synacthen test (250 μg) and the low‐dose short Synacthen test (1 μg) in assessing central adrenal insufficiency. (24th January 2014) - Cho, Hwa Y.; Kim, Jung H.; Kim, Sang W.; Shin, Chan S.; Park, Kyong S.; Kim, Seong W.; Jang, Hak‐Chul; Kim, Seong Y.
Summary Objective The short Synacthen test (SST) is widely used as alternative test to the insulin tolerance test (ITT) to investigate central adrenal insufficiency (CAI), but the methodology and cut‐off values of the SST are controversial. Our aim was to evaluate the cut‐off value of the ITT in normal subjects and to assess the different cut‐off values of the high‐dose SST (250 μg, HDT) and the low‐dose SST (1 μg, LDT) in subjects with suspected CAI. Subjects and Methods We conducted ITTs in 208 normal subjects to establish the cut‐off value for the ITT, and 28 of those subjects underwent the HDT and LDT. From 1999 to 2007, 182 patients with suspected CAI were recruited and underwent ITTs, LDTs and HDTs to establish cut‐off values and compare the diagnostic accuracy between the LDT and HDT. Results The 95th percentile of the peak cortisol level during the ITT in the normal control subjects was 14·8 μg/dl. Receiver operator characteristics (ROC) analysis revealed that the optimal cut‐off values of peak cortisol in the LDT and HDT in patients with suspected CAI were 15·8 and 17·4 μg/dl, respectively. However, the cut‐off values from normative data (mean – 2 SD) were 18·3 μg/dl for the LDT and 20·5 μg/dl for the HDT in normal control. Conclusions The optimal cut‐off values of SSTs needed to be individualized according to the type of SST and tested patient population.